2014
DOI: 10.1016/j.jped.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of erythromycin on γ-glutamyl cysteine synthetase and interleukin-1β in hyperoxia-exposed lung tissue of premature newborn rats

Abstract: Changes in oxidant-mediated IL-1 beta and GSH are involved in the development of hyperoxia-induced lung injury. Erythromycin may up-regulate the activity of γ-GCS, increasing the expression of GSH, inhibiting the levels of oxidant-mediated IL-1 beta and alleviating hyperoxia-induced lung injury via an antioxidant effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Morikawa et al ( 36 ) assessed the effect of EM in patients with diffuse panbronchiolitis and observed an increase in superoxide dismutase activity. Similarly, Cai et al ( 31 ) observed an increase in glutathione activity in rats treated with EM in a model of hyperoxia. These findings were accompanied by suppression of inflammatory cytokines and attenuation of the clinical features.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Morikawa et al ( 36 ) assessed the effect of EM in patients with diffuse panbronchiolitis and observed an increase in superoxide dismutase activity. Similarly, Cai et al ( 31 ) observed an increase in glutathione activity in rats treated with EM in a model of hyperoxia. These findings were accompanied by suppression of inflammatory cytokines and attenuation of the clinical features.…”
Section: Resultsmentioning
confidence: 75%
“…The immunomodulatory activity of EM has been extensively investigated in respiratory disorders, characterized by exacerbated inflammatory response and deleterious effects on tissues. Table 2 presents pre-clinical studies showing the effects of EM on cell function, inflammatory cytokines and oxidative stress ( 7 , 21 - 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with MPP increased cellular reduced GSH level and inhibited As(III)-induced ROS production (Figures 5(a) and 5(c) ). The upregulation of reduced GSH by MPP was consistent with its action on the increased protein level of GCLM, a key enzyme for GSH synthesis [ 48 ]. Accordingly, downregulation of ROS production by MPP inhibited As(III)-induced death and cell apoptosis (Figures 5(b) and 5(d) ).…”
Section: Discussionmentioning
confidence: 81%
“…RNA concentration can be quantified by means of a NanoDrop ND-2000 spectrophotometer (NanoDrop, Wilmington, DE). Next, reverse transcription (RT) reactions and real-time PCR were carried out in accordance with the methods described previously [12]. The expression coefficient of miRNA-574-3p and ADM relative to β-actin was calculated using the 2 − C t method.…”
Section: Total Rna Isolation and Real-time Q-pcr Verificationmentioning
confidence: 99%